A critical realist exploration of the vulnerability of staff to sexual harassment in residential long-term care. (October 2019) - Grigorovich, Alisa; Kontos, Pia
Abstract: Despite that sexual harassment of care staff negatively affects mental health and occupational outcomes, limited research has explored this in the context of residential long-term care homes. This ethnographic study explored how female care staff (e.g. providers, supervisors) understood and responded to sexual harassment from residents within the regulatory context of residential long-term care in Ontario, Canada. Data were collected from March 2017 to March 2018 and included observations and interviews with 26 staff, as well as legal, educational, and other regulatory documents. Management strategies were found to be ineffective, and despite staff acknowledgement of the negative impact of sexual harassment, they expressed tolerance of their persistent vulnerability. Drawing on critical realism, our analysis demonstrates a complex interrelationship between staff's reflexive deliberations about their experiences, health and safety regulations, and normative assumptions underpinning the education and training that they receive. Understanding the vulnerability of staff to sexual harassment at the intersection of regulation and reflexivity has important implications for the development of an effective multi-faceted approach to prevention. Highlights: Sexual harassment of care staff in long-term care is a pervasive and under-researched problem. Critical realism was used to understand the causal mechanism of vulnerability to harassment. Our findings suggest that current management strategies do not effectively protect staff. Vulnerability is produced at the intersection of regulations, norms and staff's decision-making. Prevention requires changes to education and training of staff and structural reforms.